DIFUSI INOVASI PUBLIC RELATIONS (PR) DALAM MEMANFAATKAN TEKNOLOGI TERAPAN DI PT PUTERA MULYA TERANG INDAH - Nurdansyach, Faisal Fachic; Ghassani, Rizqi (KOMUNIKA BANGSA, 2024)
The existence of a public relations division in an agency, one of which is within a company, is indeed the main point for carrying out one of the programs assigned by the company in terms of providing important information regarding developments, introducing new products and introducing new innovations to audiences such as the wider community, employees the company, therefore stakeholders can receive information conveyed directly or in the field regarding information by attending meetings or being invited directly, the role of public relations is very much considered by institutions, agencies and organizations that do have public relations in order to create good relationships , being harmonious and having chemistry are indeed the main factors in an institution, besides that the role of public relations is able to overcome or minimize problems in companies and other institutions which create sustainable relationships, public relations is also an art and social science that can be used to analyze trends , advise employees and carry out planned programs regarding activities that have the nature of serving, both the interests of organizations or institutions as well as the public interest, apart from that the relationship between community companies has needs that continue to develop and are sustainable.